Animal Domestication - Teletchea, Fabrice (IntechOpen, 2019)
Domestication, which is by definition a long ongoing process, was one of the most significant cultural and evolutionary transitions of human history, as well as a fundamental change in the evolution of the biosphere. Nevertheless, despite a vivid interest from numerous scholars, both the terms "domestication" and "domestic animal" remain confusing, and several animal groups are still poorly studied. This book contains contributions from diverse researchers and includes seven chapters, three on land animals and four on aquatic animals. The goal of this book is to stimulate fruitful exchanges to help better define the concepts of domestication and domesticated animals, and on a more applied view, help develop a more sustainable production, with animals more efficient and resilient to global change.